2020
DOI: 10.1155/2020/8836161
|View full text |Cite
|
Sign up to set email alerts
|

Learning a Second Language in Adulthood Changes Subcortical Neural Encoding

Abstract: Second language learning has been shown to impact and reshape the central nervous system, anatomically and functionally. Most of the studies on second language learning and neuroplasticity have been focused on cortical areas, whereas the subcortical neural encoding mechanism and its relationship with L2 learning have not been examined extensively. The purpose of this study was to utilize frequency-following response (FFR) to examine if and how learning a tonal language in adulthood changes the subcortical neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Our results showed that the CHY group had significantly better pitch information coding, both in magnitude and accuracy, compared to the other three groups. Considering previous studies on FFRs ( Krishnan et al, 2005 ; Liu et al, 2020 ), this was not a surprising finding. More interestingly we demonstrated how different aspects of pitch information processing capacity, namely the magnitude and accuracy, may be influenced by the aging process and language experience in similar yet different ways.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Our results showed that the CHY group had significantly better pitch information coding, both in magnitude and accuracy, compared to the other three groups. Considering previous studies on FFRs ( Krishnan et al, 2005 ; Liu et al, 2020 ), this was not a surprising finding. More interestingly we demonstrated how different aspects of pitch information processing capacity, namely the magnitude and accuracy, may be influenced by the aging process and language experience in similar yet different ways.…”
Section: Discussionsupporting
confidence: 69%
“…Wave V latencies of click-evoked ABRs were used as a benchmark for what would be considered clinically normal electrophysiological responses (no delay in wave V latencies). ABRs also serve as a quality control method for FFR recordings; a typical practice in previous works by present author(s) and others in the field ( Wang et al, 2016 ; Liu et al, 2020 ). Wave Vs of ABR for all subjects were identified by experienced audiologists.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations